IMPLEMENTATION OF DIGITAL CHILDREN'S STORY BOOKS WITH A MULTICULTURAL VALUE BACKGROUND TO DEVELOP ETHNOLITERACY FOR STUDENTS OF MLATEN STATE ELEMENTARY SCHOOL - Wawan Hermawan (LEMBAGA PENELITIAN, PENGABDIAN PADA MASYARAKAT, PENINGKATAN AKTIVITAS INSTRUKSIONAL, PENINGKATAN DAN PENJAMINAN MUTU UNIVERSITAS ISLAM MAJAPAHIT, 2025)
This community service activity aims to implement digital children's story books with multicultural values to foster student ethnoliteracy. The results of the community service activity show that there are several stages in the implementation of the activity, namely Socialization related to the product that will be implemented in schools, Training related to improving teacher competency in implementing digital books in learning, Application of technology related to the activity of applying technology in this case digital books in Indonesian language learning materials in Elementary Schools, Mentoring is carried out by the community service team to observe the application of technology in this case digital books by teachers in delivering Indonesian language learning materials, and Evaluation related to assessing the results, processes, and implementation of the application of technology in learning to find out the shortcomings and advantages; Program Sustainability is related to the continuity in implementing digital books in every learning material in Elementary Schools even though the community service activity has been completed.